The effect of Traditional Chinese Medicine on patients undergoing targeted therapy for primary liver cancer: a systematic review and meta-analysis - Yan, Hongting; Li, Yingjie; Guo, Bin; Yang, Bing; Tang, Dongxin (Frontiers in Oncology, 2025)
ObjectiveEvaluate the therapeutic efficacy and safety of Traditional Chinese Medicine (TCM) in patients with primary liver cancer (PLC) receiving targeted therapy.MethodsWe conducted a comprehensive search of databases. The search scope covered the period from the establishment of the databases to April 2025. We included 49 randomized controlled trials (RCTs) evaluating targeted therapy for primary liver cancer with TCM. Efficacy and safety outcomes were assessed using risk ratios (RR), standardized mean differences (SMD), and their 95% confidence intervals (CI).ResultsTargeted therapy for liver cancer patients who received TCM treatment showed improvements in objective response rate (ORR) (RR, 1.49 [1.33-1.66], P < 0.0001), disease control rate (DCR) (RR, 1.32 [1.25,1.40], P < 0.0001), the 1-year survival (RR, 1.50 [1.20,1.88]; P = 0.0004) and Karnofsky Performance Status (KPS) (SMD, 1.34 [0.86,1.81]; P < 0.0001), and can reduce the incidence of adverse events, as well as to some extent decrease the production of tumor markers and related inflammatory factors.ConclusionTCM enhances the efficacy and safety of targeted therapy in PLC, offering superior clinical outcomes with fewer adverse effects. These findings support its potential integration into standard treatment protocols.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251055085.